Expressão diferencial de genes associados com a resposta à infecção por Pseudocercospora fijiensis entre genótipos de bananeira - Soares, Julianna Matos da Silva (2022)
Black Sigatoka is a disease that affects the banana crop, caused by the fungus Pseudocercospora fijiensis. The fungus presents great genetic variability, culminating in the difficult control of the disease. The main banana cultivars are susceptible to this disease, for this reason there is a need to understand the mechanisms that are involved in this interaction Musa spp. x P. fijiensis. In the first chapter, information on the genetic improvement of Musa spp. in relation to black Sigatoka, compiled through a systematic review on the subject over the last ten years in six databases (PubMed Central, Web of Science, Google Academic, Springer, CAPES Periodicals and Scopus). The information gathered in this review is essential for a better understanding and direction of banana genetic improvement programs. In the review, the sites where studies on Musa x P. fijiensis have been developed, the existing sources of resistance to black Sigatoka, the study environment, the plant's defense responses during interaction and the main methodologies used in these studies were idenfied. Among the most studied genotypes, the resistant diploid Calcutta 4, widely used in breeding programs, and the susceptible triploid Grande Naine (Cavendish), used in commercial plantations for export and local consumption, stand out. In the second chapter, an experiment was carried out in order to characterize the infection process of P. fijiensis in four contrasting cultivars for resistance, in which gene expression was analyzed and histological analyzes were performed to verify the defense mechanisms activated in the plant. during the interaction. The plants were inoculated in a greenhouse and collected during five time intervals after inoculation (0, 3dpi, 9 dpi, 15 dpi, 21 dpi). Five responsive genes were used for expression analysis, which are related to the jasmonic acid and ethylene signaling pathway, GDSL lipases and pathogenesis-related proteins (PR-4). The genes showed similar upregulated expression profiles in Calcutta 4 and Krasan Saichon inoculated with P. fijiensis. Histological and histochemical studies allowed characterizing the process of infection by black Sigatoka in the studied cultivars.